If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5x-3)(5x-3)=49
We move all terms to the left:
(5x-3)(5x-3)-(49)=0
We multiply parentheses ..
(+25x^2-15x-15x+9)-49=0
We get rid of parentheses
25x^2-15x-15x+9-49=0
We add all the numbers together, and all the variables
25x^2-30x-40=0
a = 25; b = -30; c = -40;
Δ = b2-4ac
Δ = -302-4·25·(-40)
Δ = 4900
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{4900}=70$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-30)-70}{2*25}=\frac{-40}{50} =-4/5 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-30)+70}{2*25}=\frac{100}{50} =2 $
| 1.4=x-2.4 | | 12-8x=-4x-20 | | 2x+19=2x+22 | | X-7(3x+4)=4x+22 | | -3(m+7)+4(1-3m)=-7-3m+2 | | -6-5x=11-5x | | 2p^2-p+11=3 | | 12a+2=76 | | 9x-6=-x+14 | | 8x-13=x+17 | | (2x^2+4x-12)-(6x+2x^2)=x+8 | | |8x-5|=|3x+5| | | -3+2x=x+4 | | 12(x-3)=8x-9 | | 1+(5x-14)/2x=7 | | 7x=2+5 | | 6m+1=3m+10 | | 1/2x2−1/4=x | | 80x+60=20x+70 | | 12x2−14=x | | 7x-10x-2=-19 | | y+4=2y+2 | | 2(2b+2)=6(2+2b | | 1-6x=1-6x | | 7x-10(-2)=-19 | | 5x2+1=9 | | 0.5(6x-3)-x=2x+1 | | 8-3x=3-4x | | 6x-(4x+6)=8-(2x-9) | | 17t+7=34t+6 | | -3=h+8•2 | | x^2+3x+x+120=180 |